COVID-19 fear, vaccination hesitancy, and vaccination status in pregnant and breastfeeding women in Turkey - Miral, Mukaddes T.; Turgut, Nurgul; Guldur, Ayse; Guloglu, Zubeyde E.; Mamuk, Rojjin (Womens Health & Action Research Centre, 2023)
This study aimed to determine the level of COVID-19 fear, vaccination, and vaccination hesitancy as well as the affecting factors in pregnant and breastfeeding women who participated in an online prenatal education in Turkey. The study, which was designed as descriptive cross-sectional, was conducted online with 360 pregnant and breastfeeding women from Istanbul. Data were collected through the Participant Information Form, Fear of COVID-19 Scale and Vaccine Hesitancy Scale in Pandemics. The rate of accepting the COVID-19 vaccine is 65.6%. The Fear of COVID-19 Scale was 16.21 +/- 5.54, and the Vaccine Hesitancy Scale in Pandemics mean score was 29.29 +/- 4.54. The COVID-19 fear of the women participating in this study was moderate, the level of vaccination hesitancy was low, and two-thirds of them were vaccinated. There is a need to organize special counseling and vaccination campaigns for pregnant and lactating women. (Afr J Reprod Health 2023; 27 [6]: 60-69).
Keywords: COVID-19; fear; pandemic; pregnancy; vaccine; vaccine hesitancy